A Progressividade e seletividade do ICMS na energia elétrica no Pará ante a consideração do mínimo existencial - CREÃO, Alexandre Brazão (2021)
This paper seeks to expound the application and behavior of the principles of contributory capacity, selectivity, progressivity, and non-confiscation in the Brazilian legal system so that, from John Rawls‟ – Social Minimum Theory – and Amartya Sen‟s by Martha Nussbaum‟s perspective and updates – Capabilities Approach – theories of justice, it be possible to explain what the “existential minimum” is, conceptualizing it in order to know and understand the human being‟s basic necessities, and, therefore, discourse if the electric power is an essential good, both formally, as seen in laws, and materially. Therewith, and considering the large number of court lawsuits taken against the company Centrais Elétricas do Pará – CELPA, in addition to the exorbitant prices of the electricity bills, it will be verified if the State of Pará‟s Public Administration, even having arbitrated a 25-percent-aliquot of the Tax on Operations Related to the Circulation of Goods and Services Provision (ICMS) on the good in discussion, applies in its legislation the constitutional values of selectivity and progressivity when disciplining the incidence of ICMS on electricity, in order to ensure that everyone have quality access to this essential service without any extreme encumbrance in exchange, and to respect the principles of contributory capacity and non-confiscation, once both do not allow that the citizen be taxed in excess, beyond his capacity, indirectly guaranteeing the possibility of access to essential goods and services, which are necessary resources for his subsistence or his family‟s. By the end, it concludes that the State of Pará applies only the principle of progressivity, neglecting the essentiality of the electric power for the citizens‟ lives by not applying the selectivity. As solutions, it argues the possibility of the Pará government to grant tax benefits to the consumers of that service, due to the fact it is expandable the CONFAZ‟s authorization of those benefits when it comes to grant fundamental rights, bringing up as examples the following measures: the increase of the maximum limit of the ICMS-free range of consumption; and the creation of more different ranges of consumption for the application of progressive aliquots, or reduced basis of calculation, in each one of them.